Viewpoint comparison between mothers and nurses about stressor sources of parents who have premature newborn in NICU Dept - Akbarbegloo, masoomeh; valizadeh, leila; Asadollahi, malihe (Advances in Nursing & Midwifery, 2012)
Abstract Introduction: Increase of premature newborn, cause to develop research for this group of newborns. However, despite this progress, low weight and prematurity of newborns are the most important reasons for death, during the first year of their life. It seems to be important to pay close attention to the psychological and social effects of premature newborn on parents. On the other hand, investigations have showed that emotional responses of mothers in relation to premature infants born are more than fathers. Concerning special status of nurses in NICU, they have more effects in decreasing parents stress. Therefore this study has been performed to recognize viewpoints of mothers and nurses about stress in NICU for decreasing parental stress. Method: This is a comparative-descriptive study, that has been done during the first 6 months in year 2007, and the study population consisted of nurses (n=32) and all mothers with premature newborn, hospitalized in NICU (n=300) in three training centers - Health in Tabriz (Taleghani, Alzahra, Koodakan). Sampling method was census and data collected by PSS (parent stressor scale) questionnaire, developed by Margaret Miles et al in 1998. Validity of scale was determined by content validity with cooperation of ten faculty members of Nursing-Midwifery college of Tabriz, and validity of translation assessed by one English language expert. Reliability of scale was evaluated by participation of 30 mothers and 6 nurses which the related method was Cronbach's alpha, (for mothers calculated, 0/87 and for nurse 0/94). Data was analyzed by SPSS version 13.5 software. Results: For viewpoint of mothers and nurses, Mann-Whitney U test showed that, there are significant difference between three ranges of stressors, and for viewpoint of mothers, Friedman test showed that, the most stressor sources were “relationship of parents and parental role” and for viewpoint of nurses, were “baby appearances and behavior, and special treatments” and “relationship of parents and parental role”. Conclusion: Accurate researches of parent stressor, specially, mothers who have premature newborn, to introduce solutions for family cares and satisfaction increase is very necessary and important. Keywords: Premature infant .Stressors. Mother. Nurse .Intensive care unit